Strengthening Legal Instruments Plagiarism Threshold in the Field of Education and Digital - Luhukay, Roni Sulistyanto; Marsal, Antonino Pedro (JURNAL AKTA, 2025)
Plagiarism is a detrimental act in the world of education, especially in the digital era that facilitates access to information. Technological advances make people tend to choose shortcuts by copying other people's work without mentioning the source. Plagiarism reduces critical thinking, which should be part of the learning process, and inhibits the development of creativity and intellectual abilities. This practice not only damages academic integrity, but also lowers the quality of education and the reputation of the institution. This research uses a normative legal research method that analyses the applicable legal rules and evaluates the provisions regarding plagiarism in education, especially in the digital context. This research discusses how the phenomenon of plagiarism in education reflects the lack of clear regulations regarding the threshold of plagiarism in Indonesia. This lack of clarity causes difficulties in distinguishing between legitimate use of information and plagiarism, especially in the midst of easy digital access. In addition, more sophisticated plagiarism detection technology and digital ethics education need to be strengthened as preventive measures. International co-operation is also important to address cross-border plagiarism. A holistic approach is expected to create a more honest, transparent, and integrity-based educational environment.